Clinical and Molecular Evaluation of SHOX/PAR1 Duplications in Léri-Weill Dyschondrosteosis (LWD) and Idiopathic Short Stature (ISS) - Sara Benito‐Sanz; Eva Barroso; Damián Heine‐Suñer; Alfonso Hisado-Oliva; Valeria Romanelli; Jordi Rosell; Ángel Aragonés; María Caimari; Jesús Argente; Judith L. Ross; Andrew R. Zinn; R Gracia; et al. (2010)
Léri-Weill dyschondrosteosis (LWD) is a skeletal dysplasia characterized by disproportionate short stature and the Madelung deformity of the forearm. SHOX mutations and pseudoautosomal region 1 deletions encompassing SHOX or its enhancers have been identified in approximately 60% of LWD and approximately 15% of idiopathic short stature (ISS) individuals. Recently SHOX duplications have been described in LWD/ISS but also in individuals with other clinical manifestations, thus questioning their pathogenicity.The objective of the study was to investigate the pathogenicity of SHOX duplications in LWD and ISS.Multiplex ligation-dependent probe amplification is routinely used in our unit to analyze for SHOX/pseudoautosomal region 1 copy number changes in LWD/ISS referrals. Quantitative PCR, microsatellite marker, and fluorescence in situ hybridization analysis were undertaken to confirm all identified duplications.During the routine analysis of 122 LWD and 613 ISS referrals, a total of four complete and 10 partial SHOX duplications or multiple copy number (n > 3) as well as one duplication of the SHOX 5' flanking region were identified in nine LWD and six ISS cases. Partial SHOX duplications appeared to have a more deleterious effect on skeletal dysplasia and height gain than complete SHOX duplications. Importantly, no increase in SHOX copy number was identified in 340 individuals with normal stature or 104 overgrowth referrals.MLPA analysis of SHOX/PAR1 led to the identification of partial and complete SHOX duplications or multiple copies associated with LWD or ISS, suggesting that they may represent an additional class of mutations implicated in the molecular etiology of these clinical entities.